Distribution of the Crustal Magnetic Field in Sichuan-Yunnan Region, Southwest China. (26th August 2014) - Bai, Chunhua; Kang, Guofa; Gao, Guoming
Abstract : Based on the new and higher degree geomagnetic model NGDC-720-V3, we have investigated the spatial distribution, the altitude decay characteristics of the crustal magnetic anomaly, the contributions from different wavelength bands to the anomaly, and the relationship among the anomaly, the geological structure, and the geophysical field in Sichuan-Yunnan region of China. It is noted that the most outstanding feature in this area is the strong positive magnetic anomaly in Sichuan Basin, a geologically stable block. Contrasting with this feature, a strong negative anomaly can be seen nearby in Longmen Mountain block, an active block. This contradiction implies a possible relationship between the magnetic field and the geological activity. Completely different feature in magnetic field distribution is seen in the central Yunnan block, another active region, where positive and negative anomalies distribute alternatively, showing a complex magnetic anomaly map. Some fault belts, such as the Longmen Mountain fault, Lijiang-Xiaojinhe fault, and the Red River fault, are the transitional zones of strong and weak or negative and positive anomalies. The corresponding relationship between the magnetic anomaly and the geophysical fields was confirmed.